Real Time Emotion Recognizer And Classifier For Facial Expressions Based On Machine Learningapproach - et. al., K.Balasaranya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are various fields in deep learning that are known for their big success one such technique is computer vision. In computer vision the detection of face emotion is done using the convolutional neural networks technique where the model can be trained to analyze images or videos. In this paper we propose a system that recognizes the emotions that a person is having at any point of time by checking the emotion from frame to frame in a video medium. It consist of a multistage image processing to extract feature representations. We characterize six emotions based on the boundary of the face and compare it with the existing databases to get the most accurate emotion from the six.